Sperm-Specific Glycolysis Enzyme Glyceraldehyde-3-Phosphate Dehydrogenase Regulated by Transcription Factor SOX10 to Promote Uveal Melanoma Tumorigenesis - Ding, Xia; Wang, Lihua; Chen, Mingjiao; Wu, Yue; Ge, Shengfang; Li, Jin; Fan, Xianqun; Lin, Ming (Frontiers in Cell and Developmental Biology, 2021)
Melanoma cells exhibit increased aerobic glycolysis, which represents a major biochemical alteration associated with malignant transformation; thus, glycolytic enzymes could be exploited to selectively target cancer cells in cancer therapy. Sperm-specific glyceraldehyde-3-phosphate dehydrogenase (GAPDHS) switches glyceraldehyde-3-phosphate to 1,3-bisphosphoglycerate by coupling with the reduction of NAD+ to NADH. Here, we demonstrated that GAPDHS displays significantly higher expression in uveal melanoma (UM) than in normal controls. Functionally, the knockdown of GAPDHS in UM cell lines hindered glycolysis by decreasing glucose uptake, lactate production, ATP generation, cell growth, and proliferation; conversely, overexpression of GAPDHS promoted glycolysis, cell growth and proliferation. Furthermore, we identified that SOX10 knockdown reduced the activation of GAPDHS, leading to an attenuated malignant phenotype, and that SOX10 overexpression promoted the activation of GAPDHS, leading to an enhanced malignant phenotype. Mechanistically, SOX10 exerted its function by binding to the promoter of GAPDHS to regulate its expression. Importantly, SOX10 abrogation suppressed in vivo tumor growth and proliferation. Collectively, the results reveal that GAPDHS, which is regulated by SOX10, controls glycolysis and contributes to UM tumorigenesis, highlighting its potential as a therapeutic target.